Reduction of the domains of basic elementary functions to arbitrary small intervals - Shishkov, Dimitar (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 1995)
Algorithms for reduction of the initially constraint unlimited domains of basic elementary functions of the system $\{e^x, \ln x, \tg x, \sin x, \cos x, \arcsin{x}\}$ to sufficiently small intervals are treated.